2020
DOI: 10.1123/ijsnem.2019-0237
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Exercise Timing on Chemosensory Response, Appetite, and Energy Intake in Lean Males

Abstract: Background: High-intensity exercise can have an anorectic impact, leading to negative energy balance. Several studies have reported that the practice of physical activity could also cause a shift in perceptions and preferences, causing a change in food intakes. Objective: This study aimed to question to what extent the timing of exercise in relation to a meal could have an impact on olfaction and gustation, appetite, and food choices. Methods: Twelve males aged 25 (4) years with a body mass index of 22.4 (2.0)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
29
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(29 citation statements)
references
References 40 publications
0
29
0
Order By: Relevance
“…From the 5699 titles screened, 88 were approved based on their title, 49 were assessed using the full text, and 18 were analyzed and included in this systematic review. From the 18 studies, 17 had an experimental design, including non-defined [18], nonrandomized control trials [16,17,[19][20][21][22][23][24][26][27][28]30,32,33], and randomized control trials [25,31]. One case control study [29] was also included.…”
Section: Study Selectionmentioning
confidence: 99%
See 2 more Smart Citations
“…From the 5699 titles screened, 88 were approved based on their title, 49 were assessed using the full text, and 18 were analyzed and included in this systematic review. From the 18 studies, 17 had an experimental design, including non-defined [18], nonrandomized control trials [16,17,[19][20][21][22][23][24][26][27][28]30,32,33], and randomized control trials [25,31]. One case control study [29] was also included.…”
Section: Study Selectionmentioning
confidence: 99%
“…The studies originated from Canada [33], China [29], Ireland [32], Israel [21,22], Japan [18,19,23,26,28], the Netherlands [25], New Zealand [30], Norway [31], the United States of America [16,17,24,27], and the United Kingdom [20]. Most of the studies were conducted on healthy normal-weight males and females, but some studies included participants who were obese [31], clinically ill [29], or athletic [16,24,26,27].…”
Section: Study and Intervention Characteristicsmentioning
confidence: 99%
See 1 more Smart Citation
“…Some studies have been specifically conducted to compare some nutritional outcomes in response to exercise depending on its delay with a meal. In their work, Josaphat and collaborators asked healthy men to perform an acute 30-minute exercise set at 70% of their maximal aerobic capacities either 90 minutes or right before a lunch test meal [37]. According to their results, there was no difference between the two conditions regarding total ad libitum energy intake, appetite feelings and the taste or smell sensations [37].…”
Section: The Exercise-meal Delaymentioning
confidence: 99%
“…In their work, Josaphat and collaborators asked healthy men to perform an acute 30-minute exercise set at 70% of their maximal aerobic capacities either 90 minutes or right before a lunch test meal [37]. According to their results, there was no difference between the two conditions regarding total ad libitum energy intake, appetite feelings and the taste or smell sensations [37]. Interestingly, using a similar design, Albert et al observed a reduction of 11% of the post-exercise energy intake (with a 23% decrease in ingested fat) when the exercise (30 minutes treadmill running at 70% VO 2max ) is performed just before the meal compared with 165 minutes before, with no difference regarding appetite feelings, in normal-weight adolescents [38].…”
Section: The Exercise-meal Delaymentioning
confidence: 99%